When the Blue Marble Health concept challenges our current understanding of One Health - Marine Combe; Rodolphe Elie Gozlan (One Health)
We address the issue of reconciling the hygienist and dilutionist (H&D) perspectives for a global understanding of health as envisioned in the One Health framework. Rich and poor countries share pockets of poverty on the outskirts of urban centres, known as ‘infectious bubbles’, which remain high-risk areas for disease emergence due to a common failure of both the H&D perspectives. People living in these IBs are exposed to infectious microbes on a daily basis due to inadequate hygiene infrastructure, while at the same time lacking a heathy nature to act as a buffer through a dilution effect. The Blue Marble Health approach shows that the burden of neglected diseases has also been neglected in rich countries. We argue for a single health framework that incorporates a mixed model of H&D views and addresses the issue of IB in the distribution and endemicity of emerging infectious diseases in large developed cities.